Summertime ozone pollution in Sichuan Basin, China: Meteorological conditions, sources and process analysis. (1st April 2020) - Yang, Xianyu; Wu, Kai; Wang, Haolin; Liu, Yiming; Gu, Shan; Lu, Yaqiong; Zhang, Xiaoling; Hu, Yishi; Ou, Yihan; Wang, Shigong; Wang, Zhanshan
Abstract: The Sichuan Basin (SCB) has suffered from serious ozone (O3 ) pollution in recent years, especially in summer. However, the formation and evolution mechanisms of O3 pollution in the SCB remain poorly understood. In this paper, we comprehensively investigated the causes of elevated ozone concentrations in Chengdu in July 2017 with a combination of field measurements and the WRF (Weather Research and Forecasting)-CMAQ (Community Multi-scale Air Quality) model simulations. The ozone formation characteristics of continuous O3 episodes and non-O3 episodes were compared. Higher temperature (T), stronger solar radiation (SR), lower relative humidity (RH) and weaker winds were conducive to O3 formation during ozone episodes. The O3 concentration during O3 episodes (202.6 μg m −3 ) was significantly higher than that during non-O3 episodes (122.7 μg m −3 ), attributable to the higher volatile organic compounds (VOCs) concentration (34.0 ppbv compared with 27.5 ppbv) despite comparable NO x concentrations during O3 episodes. The results of positive matrix factorization (PMF) for ambient VOCs showed that gasoline vehicle exhaust and solvent usage were the dominant sources during the month. However, the increasing source attributions from the petrochemical industry and biogenic emissions were responsible for the elevated VOCs concentrations during O3 episodes. The relative contributions of local emission and regional transport to ozone were quantified during two O3 episodes by conducting numerical sensitivity experiments. In the first episode, namely, the "O3 -regionally transported" pattern, high ozone concentration in Chengdu was primarily due to the regional transport of ozone and ozone precursors through vertical mixing and horizontal advection from upwind areas (central and eastern SCB) when easterly or southeasterly winds prevailed over the SCB. In contrast, in the second episode, namely, the "O3 -locally dominated" pattern, high local emissions under favorable meteorological conditions are the major reason for elevated ozone concentration. The process analysis results from the CMAQ model suggested that the vertical transport of O3 that formed at the upper levels from intense gas-phase chemistry reactions was a dominant contributor to diurnal O3 enhancement in O3 episodes by 45 μg m −3, while horizontal transport contributed more than 80% of the nocturnal O3 concentration. This study provides a better understanding of ozone photochemical formation and regional transport mechanisms in the SCB under complex terrain conditions, and contributes to ozone pollution prevention in other basins around the world. Highlights: Two high O3 episode in Chengdu was simulated using the WRF-CMAQ modeling system. Ozone and precursors from upwind-polluted areas are crucial to high ozone episodes in Chengdu. Vertical mixing plays an important positive role to surface elevated ozone in Chengdu.